INTEGRATION OF ARTIFICIAL INTELLIGENCE IN THE ISLAMIC RELIGIOUS EDUCATION CURRICULUM: OPPORTUNITIES, CHALLENGES, AND IMPLICATIONS - Thahirrah, Al Athiyyah Thahirrah; Erni Kasmawati; Junaidi (BiCED Proceeding, 2025)
This study focuses on the integration of Artificial Intelligence (AI) in the Islamic Religious Education (IRE) curriculum, examining the opportunities, challenges, and implications of AI application for the transformation of religious education in the digital age. The novelty of this study lies in its comprehensive review that combines technological, pedagogical, and Islamic values aspects in the IRE curriculum, which has been little studied in depth. The method used is literature research with structured literature studies from various relevant sources. The results show that AI has great potential in personalizing learning, increasing access and interactivity of materials, and strengthening Islamic digital literacy and digital ethics. However, there are major challenges in the form of teacher readiness, infrastructure limitations, ethical issues in the use of AI, and the need to adapt the curriculum based on the values of the Quran and hadith. The implications of AI integration include adaptive curriculum renewal, teacher training, and collaboration between the fields of education and technology to support relevant and comprehensive education. This study provides strategic guidance for Islamic educational institutions in responding to the era of education 5.0, which emphasizes a balance between technology and Islamic values.